2021
DOI: 10.1007/s00284-021-02654-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Underlying the Role of LuxR Family Transcriptional Regulator abaR in Biofilm Formation by Acinetobacter baumannii

Abstract: Our study attempted to explore the mechanism underlying the role of LuxR family transcriptional regulator abaR in biofilm formation by Acinetobacter baumannii. The abaR gene was knocked out in ATCC 17978 strain using homologous recombination method. The growth curve and biofilm formation were measured in the wild type and abaR gene knockdown strains. Transcriptome sequencing was performed in the wild type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The only reported QS-system in A. baumannii is AbaI/R which closely regulates various virulence factors including biofilm formation. It is reported that abaI mutants were less virulent than wild type and an AbaR mutant formed lesser biofilms comparatively [77,78]. Therefore, we screened the effect of 2,4-DBP on abaI and abaR expression.…”
Section: Discussionmentioning
confidence: 99%
“…The only reported QS-system in A. baumannii is AbaI/R which closely regulates various virulence factors including biofilm formation. It is reported that abaI mutants were less virulent than wild type and an AbaR mutant formed lesser biofilms comparatively [77,78]. Therefore, we screened the effect of 2,4-DBP on abaI and abaR expression.…”
Section: Discussionmentioning
confidence: 99%